2008
DOI: 10.3136/fstr.14.589
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hanabiratake (Sparassis crispa) on Allergic Rhinitis in OVA-Sensitized Mice

Abstract: The anti-rhinitis properties of Sparassis crispa were investigated in mice. To examine the immunomodulative activity of oral administration of S. crispa, splenocytes obtained from ovalbumin-sensitized BALB/ c mice fed S. crispa were restimulated in vitro with the same antigen. Oral administration of S. crispa induced IFN-γ, but inhibited IL-4 and IL-5 secretion, and suppressed ovalbumin-specific IgE secretion by ovalbumin-stimulated splenocytes. The effects of S. crispa were further investigated by using the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…The primary structure of β-glucan isolated from SC was a 6-branched 1, 3-β-glucan, having one branch in every third main-chain [27]. SC has been reported to have many biological effects such as tumor suppression [8], anti-allergy [33], and wound-healing [13], as well as enhancements in hematopoietic responses [7]. In a clinical trial, β-glucan itself had strong anticancer effects on patients with lung, stomach, colon, breast, and prostate cancers [21].…”
Section: Introductionmentioning
confidence: 99%
“…The primary structure of β-glucan isolated from SC was a 6-branched 1, 3-β-glucan, having one branch in every third main-chain [27]. SC has been reported to have many biological effects such as tumor suppression [8], anti-allergy [33], and wound-healing [13], as well as enhancements in hematopoietic responses [7]. In a clinical trial, β-glucan itself had strong anticancer effects on patients with lung, stomach, colon, breast, and prostate cancers [21].…”
Section: Introductionmentioning
confidence: 99%
“…The chemical structures of the isolated compounds (1)(2)(3)(4)(5)(6) are shown in Fig. 1 br s), and an aromatic proton at d 6.85 (1H, br s).…”
Section: Chemical Characterizations Of Isolated Compoundsmentioning
confidence: 99%
“…SC grows primarily on the stumps of coniferous trees and is abundant in northern temperate zones throughout the world. 2-4) SC has been reported to have many biological effects such as tumor-suppressing effects, 2,4,5) effects in improving natural killer cell activity, 5) anti-angiogenic effects, 4) anti-allergic effects, 6) wound-healing effects, 7) and effects in enhancing hematopoietic responses. 2,8) In addition, a recent study suggested that the administration of b-D-glucan from SC could be an effective treatment strategy for cancer patients.…”
mentioning
confidence: 99%
“…[11][12][13] SC has been reported to have many biological activities such as tumor-suppressing effects, 11,13,14) improve- Vol. 56 (2010) ment in natural killer cell activity, 14) antiangiogenic effects, 13) antiallergic effects, 15) wound healing effects, 16) and enhancements in hematopoietic responses. 11,17) However, no studies have been performed to elucidate the antidiabetic properties of SC.…”
Section: Introductionmentioning
confidence: 99%